AGENDA KEBIJAKAN LUAR NEGERI INDONESIA PASCA PEMILIHAN PRESIDEN 2009 - Effendi, Tonny Dian (Jurnal Bestari, 2009)
There are so many unsolved problems in Indonesian's foreign policy. Some analysts told that Indonesian's foreign policy has no profile in post reformation, comparing with the two regimes before. The problem is about the profile that have to be built by the government to show Indonesian's position in international view. In Indonesian's foreign policy, it looks like that there is no principle in its relations especially with the western countries. Administration system of the recent president actually has opportunity to change the problem for there is a democracy development that has been appreciated by international forums. In some field, it showed that Indonesian's foreign policy also depends on the executive institution. So, for the next president and for he/her administrations, there are some agendas that based on three points. Those are an equal position between foreign and domestic priority, domestic empowerment for the consistency and supported Indonesian's diplomacy by implementing total diplomacy, and increasing the international knowledge for society and the local staff in the context of local autonomy.